DESIGNING THE MUSIC COLLEGE IN CENTRAL JAKARTA - Shania Noor Aisyah; Anedya Wardhani; Ni Wayan Ardini (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: This paper was written with the aim of providing a forum that is able to facilitate the enthusiasm of the community, especially in Central Jakarta, in developing their music education after graduating from SMA / SMK equivalent to a higher level to produce potential and quality graduates. Research methods: The research method used in the design uses location data obtained online to take aerial photos of the site, then combined with architectural theory studies, music theory and comparative studies of similar buildings. Findings: The results will then be analyzed to produce a design concept. The design concept combines the order of the structure in the music consisting of an intro, verse, bridge, chorus, and ending. The concept is applied to the zoning order of the site. The composition of the building mass is also inspired by the form of musical notes that are processed based on different functions. Implications: The expressionism design theme is very appropriate to represent the character of the building to make it more iconic and dynamic. The results of the design process are in the form of concepts, working drawings, perspective drawings, and animated videos.